Selected Abstracts of the 2nd Congress of joint European Neonatal Societies (jENS 2017); Venice (Italy); October 31-November 4, 2017; Session "Neonatal Hematology and Bilirubin" - - (Hygeia Press di Corridori Marinella, 2017)
Selected Abstracts of the 2nd Congress of joint European Neonatal Societies (jENS 2017); Venice (Italy); October 31-November 4, 2017 58th ESPR Annual Meeting, 7th International Congress of UENPS, 3rd International Congress of EFCNI ORGANIZING INSTITUTIONS European Society for Paediatric Research (ESPR), European Society for Neonatology (ESN), Union of European Neonatal & Perinatal Societies (UENPS), European Foundation for the Care of Newborn Infants (EFCNI) ORGANIZING COMMITTEE Luc Zimmermann (President of ESPR), Morten Breindahl (President of ESN), Manuel Sánchez Luna (President of UENPS), Silke Mader (Chairwoman of the Executive Board and Co-Founder of EFCNI) SCIENTIFIC COMMITTEE Virgilio P. Carnielli (Congress President Chair), Pierre Gressens (Past Scientific President), Umberto Simeoni, Manon Benders, Neil Marlow, Ola D. Saugstad, Petra Hüppi, Agnes van den Hoogen Session "Neonatal Hematology and Bilirubin" ABS 1. PROLONGED JAUNDICE SCREENING: FULL BLOOD COUNT (FBC) OR NO FBC! • N. Storring, R. Doherty, V. Ponnusamy ABS 2. EFFECT OF PROBIOTIC SUPPLEMENTATION ON BREAST MILK JAUNDICE • N. Koksal, O. Bagcı, H. Ozkan, I. Varal, P. Dogan ABS 3. LABORATORY FINDINGS, DIAGNOSIS AND TREATMENT OF THE NEWBORN ADMITTED DUE TO HEMATEMESIS OR BLOODY STOOL IN 11 YEARS • I. Hokuto, Y. Ito, T. Mori, S. Komachi ABS 4. AN UNUSUAL CAUSE OF CYANOSIS: SEVERE METHEMOGLOBINEMIA IN A PRETERM INFANT WITH SEPSIS • F. Bakar, M. Berber ABS 5. THE INFLUENCE OF INTRAUTERINE TRANSFUSION ON THE OUTCOMES OF NEWBORNS WITH SEVERE HEMOLYTIC DISEASE • E. Balashova, O. Bystrykh, T. Fedorova, O. Ionov, A. Kirtbaya, D. Sharafutdinova, V. Zubkov, D. Degtyarev, O. Horoshkeeva, N. Fedorova, N. Tetruashvili, K. Kostukov, N. Karetnikova ABS 6. PATCHED SKIN BILIRUBIN ASSAY TO MONITOR EXTREMELY PRETERM NEONATES UNDERGOING PHOTOTHERAPY • D. De Luca, V. Dell'Orto ABS 7. A PRETERM MODEL OF HYPERBILIRUBINEMIA-INDUCED CEREBELLAR DYSFUNCTION • C.F. Bearer, M. He, J.F. Watchko, J.M. Simard, N. Tang ABS 8. PHYSIOLOGIC FREE BILIRUBIN REDISTRIBUTES L1 CELL ADHESION MOLECULE (L1) IN LIPID RAFTS • N. Tang, M. He, J.F. Watchko, C.F. Bearer ABS 9. RETICULOCYTE HEMOGLOBIN CONTENT AS AN EARLY INDEX OF IRON DEFICIENCY IN NEONATAL PERIOD • P. Karagianni, E. Chatzitoliou, V. Antari, M. Lithoxopoulou, G. Mitsiakos, C. Tsakalidis, A. Kioumi, V. Soubasi ABS 10. PREDICTION OF MAJOR BLEEDING IN EXTREMELY LOW BIRTH WEIGHT INFANTS (< 1,000 g) BY SEQUENTIAL COAGULATION MONITORING • M. Thanhaeuser, C. Binder, M. Kornsteiner-Krenn, U. Derhaschnig, B. Jilma, A. Repa, A. Berger, N. Haiden ABS 11. IV FLUID SUPPLEMENTATION IN SEVERE NEONATAL HYPERBILIRUBINEMIA: YES OR NO • M.T. Saleh, S. El Doory, S. Saleh, Mel. Halik ABS 12. RIGHT SUBCLAVIAN ARTERY THROMBOSIS. A CASE REPORT • G. Uclés, T. Fuentes, R. Villarino, M. González-Valcárcel, A. Martínez ABS 13. RISK FACTORS FOR PORTAL VENOUS THROMBOSIS IN NEWBORNS: A RETROSPECTIVE STUDY • A. Zanin, M. Colella, C. Farnoux, S. Soudee, M. Leport, R. Stern, O. Bequet, M. Alison, V. Biran, O. Baud ABS 14. COMPARISONS BETWEEN TRANSCUTANEOUS BILIRUBINOMETRY, POINT-OF-CARE WHOLE BLOOD BILIRUBIN AND TOTAL PLASMA BILIRUBIN MEASUREMENT IN NEONATES • K. Palmkvist Kaijser, C. Backman Johansson, K. Hemse Nojd, C. Bemgard, K. Kjellson, G. Marchini ABS 15. RELATIONSHIP BETWEEN PLASMA LEVELS OF BILIRUBIN AND OXIDANT/ANTIOXIDANT STATUS IN THE EARLY NEONATAL PERIOD IN PRETERM INFANTS • G.I. Zoutkamp, K. Suzuki, C.H.P. van den Akker ABS 16. RELATIONSHIP BETWEEN LEUKOCYTES AND PLATELETS AND PREMATURE RETINOPATHY • V. Filip, C. Lazar ABS 17. CONGENITAL HEPATOCELLULAR CARCINOMA ASSOCIATED WITH NEONATAL HEMOCHROMATOSIS • P. Francalanci, C. Grimaldi, M.C. Saffioti, R. Angelico, R. Boldrini, F. Callea ABS 18. INVESTIGATION OF THE RELATIONSHIP BETWEEN UMBILICAL CORD BLOOD RMI LEVEL AND PERINATAL EVENTS • Z.E. Erdem Dursun, N. Guzoglu, D. Aliefendioglu ABS 19. OUTCOME OF BABIES WITH SERUM BILIRUBIN LEVEL OF GREATER THAN 400 MICROMOL/L • R. Prasad, S.V. Rasiah ABS 20. AN AUDIT OF USE OF EMERGENCY 0 NEGATIVE BLOOD IN NEONATES FOR EMERGENCY BLOOD TRANSFUSIONS AND EXCHANGE TRANSFUSIONS • P. Tormey, D. Sweetman, J. Quigley, J. Fitzgerald ABS 21. THE COAGULATION SCREEN AS A BIOMARKER OF NEONATAL ENCEPHALOPATHY OUTCOMES • D. Sweetman, J. Murphy, E.J. Molloy